The Earth Microbiome project: successes and aspirations - Gilbert, Jack A; Jansson, Janet K; Knight, Rob (BMC biology, 2014)
The Earth Microbiome Project (EMP) was launched in August 2010, with the ambitious aim of constructing a global catalogue of the uncultured microbial diversity of this planet. The primary vision of the Earth Microbiome Project, to process the microbial diversity and functional potential from approximately 200,000 environmental samples, marks it as an undertaking so massive that it was at first considered to be pure folly (as late as 2012, Jonathan Eisen was quoted in Nature as saying Knight and Gilbert literally talk about sampling the entire planet. It is ludicrous and not feasible - yet they are doing it [1]).